2011
DOI: 10.1093/schbul/sbr071
|View full text |Cite
|
Sign up to set email alerts
|

Social-Cognitive Remediation in Schizophrenia: Generalization of Effects of the Training of Affect Recognition (TAR)

Abstract: In the last decade, several social cognitive remediation programs have been developed for use in schizophrenia. Though existing evidence indicates that such programs can improve social cognition, which is essential for successful social functioning, it remains unclear whether the improvements generalize to social cognitive domains not primarily addressed by the intervention and whether the improved test performance transfers into everyday social functioning. The present study investigated whether, beyond its k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
58
1
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(70 citation statements)
references
References 60 publications
3
58
1
8
Order By: Relevance
“…The performance in ToM was impaired in schizophrenia, even in patients who were completely free of residual symptoms (Bora et al, 2008). Furthermore, evidence that social cognitive remediation improves EP in patients with schizophrenia exists; however, ToM is difficult to improve with social cognitive remediation compared with other social cognitive domains (Horan et al, 2011;Wölwer and Frommann, 2011). However, the present study demonstrated that the performance in AB in individuals at CHR was most impaired among the social cognitive domains.…”
Section: Discussionmentioning
confidence: 48%
“…The performance in ToM was impaired in schizophrenia, even in patients who were completely free of residual symptoms (Bora et al, 2008). Furthermore, evidence that social cognitive remediation improves EP in patients with schizophrenia exists; however, ToM is difficult to improve with social cognitive remediation compared with other social cognitive domains (Horan et al, 2011;Wölwer and Frommann, 2011). However, the present study demonstrated that the performance in AB in individuals at CHR was most impaired among the social cognitive domains.…”
Section: Discussionmentioning
confidence: 48%
“…No other significant effect in social cognition measures were found with the NPT-MH training. ToM, and to a less degree attributional biases, have been found to improve after SCT in schizophrenia patients (Penn et al, 2007;Wolwer and Frommann, 2011;Bechi et al, 2012), but, to our knowledge, CRT or SCT effects in these social cognition domains in early-stages psychosis have not been studied yet.…”
Section: Discussionmentioning
confidence: 86%
“…SCT seem to impact in ToM alterations (Wolwer and Frommann, 2011;Bechi et al, 2012), emotional processing deficits, attributional biases (Penn et al, 2007) as well as functional outcomes (Wolwer and Frommann, 2011;Tas et al, 2012). There are several studies using SCT in the early phases of schizophrenia, but no SCT programs specifically designed for patients at early stages of psychosis currently exist.…”
Section: Introductionmentioning
confidence: 99%
“…To the extent that emotion recognition deficits do contribute directly to development of psychosis, early detection may be critical to permit timely intervention. Recent studies suggest that impaired face emotion recognition may be remediable, with generalization of effect including improved prosody and social function (Wolwer & Frommann, 2011), and normalization of activity in the face-processing network (Habel et al 2010). Implementation of such efforts during the CHR period may thus be critical for altering long-term course.…”
Section: Discussionmentioning
confidence: 99%